Teenage Pregnancy: Obstetric and Perinatal Outcome in a Tertiary Centre in Indonesia - Junita Indarti; Adly Nanda Al Fattah; Zulfitri Dewi; Rachmat Dediat Kapnosa Hasani; Fitri Adinda Novianti Mahdi; Raymond Surya (Obstetrics and Gynecology International)
Background. The incidence of teenage pregnancy is increasing in the world. It is a high-risk condition leading to adverse perinatal and obstetric outcomes. This study aims to evaluate the obstetric and perinatal outcomes of teenage pregnancy in Indonesian population. Method. A retrospective study was conducted to evaluate obstetric and perinatal outcomes among teenagers and average maternal age (AMA) women. We assessed all singleton live pregnancies during the year period of 2013 in Dr. Cipto Mangunkusumo National General Hospital, Jakarta, Indonesia. Results. We studied 1,676 eligible subjects during the one-year period in our centre. The prevalence of teenage pregnancy (12 to 19 years old) was 11.40% (191/1676). We found higher prevalence of eclampsia (AOR: 4.03; 95% CI: 1.73–9.39), preterm delivery (AOR: 1.5; 95% CI: 0.88–2.53), anaemia at labour (AOR: 2.42; 95% CI: 1.60–3.67), postpartum haemorrhage (AOR: 2.59; 95% CI: 0.86–7.37), and low birth weight (AOR: 2.28; 95% CI: 1.60–3.25) among teenagers. However, caesarean section was found to be significantly lower among teenage pregnancies. Conclusion. Teenage pregnancy carries significant obstetric complications that should draw physicians’ serious attention. A holistic, comprehensive antenatal, and preventive program should be conducted to prevent teenage pregnancy-related adverse outcomes.